Symptoms of anxiety and depression associated with concerns about infection and gender-based violence during the COVID-19 pandemic - Machado, Daiane Borges; da Silva Rodrigues, Elisângela; Barbosa, Jakeline Ribeiro; de Oliveira Alves, Flavia Jôse; Gonçalves, Alessandra Queiroga; Duarte-Salles, Talita; Aviñó, Constanza Jacques; Berenguera, Anna; Passos , Maria Fabiana Damasio; Barreto , Maurício Lima; Castro-de-Araujo, Luis Fernando Silva (International Journal of Population Data Science, 2022)
Background It is known that the COVID-19 pandemic and social isolation has increased anxiety, depression, and gender-based violence. However, to the best of our knowledge no studies have evaluated differences in the association between anxiety and depression symptomatology with concern about becoming infected with COVID-19, and the differential risk of suffering from gender-based violence among women with a previous mental disorder, and black women. Methods We conducted a cross-sectional study among adults living in Brazil during the COVID-19 lockdown (20th June-30th August 2020). We administered an online questionnaire containing questions on socioeconomic characteristics, risk perception, confinement, health conditions, and gender-based violence. We ran two ordinal logistic regression models. In the first, we considered having a previous mental disorder and sex as the predictors, and concern about becoming infected with COVID-19 as the outcome. In the second model, we considered previous mental disorders and race as the predictors, and gender-based violence as the outcome. Depressive symptomatology and anxiety symptomatology was assessed through PHQ-9 and GAD-7, respectively. Findings People who declared that they suffered from depression had a 2% less chance of concern about becoming infected with COVID-19, while those with anxiety had an 11% higher chance. Women had 19% more chance of being very concerned about becoming infected with COVID-19, compared to men. Women with previous mental health disorders had a 34% higher chance of suffering from gender-based violence, compared to women who did not declare having a previous mental health disorder. Black women had a 54% higher chance of suffering from gender-based violence during the COVID-19 pandemic, compared to white women. Conclusions This is the first study to demonstrate that black women and those with mental health problems are more likely to suffer from gender- based violence during the pandemic. These findings could be used in the preparation of protection policies focused on women in situations of major vulnerabilities, optimising interventions and enhancing resource allocation for those most in need, especially during pandemics.